Assessment of COVID-19 Severity Using Chest CT Severity Score on High-Resolution Computed Tomography Chest in Pakistani Patients - Sidra Afzal, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The current review aims at portraying the high-resolution CT (HRCT) chest findings of corona virus pandemic that emerged in 2019 amongst the COVID-19 patients, admitted to the tertiary healthcare facilities in Punjab, Pakistan. It also aims to study the imaging features and dispensation of COVID-19 infection in different segments of the lungs. Moreover, a survey was also conducted for the job to analyze the chest CT severity score index (CT-SS) aims at identifying those patients with acute infections. Methods: This cross-sectional descriptive analysis led from May 15, 2020 to November 26, 2021, incorporates 97 diagnosed patients of the COVID-19 who received the HRCT scan in the tertiary healthcare facilities in Punjab, Pakistan. The HRCT chest of the infected patients was collected following the proper protocol. Each case was assessed for the presence of imaging features such as ground glass opacities (GGOs), consolidation, mixed pattern, crazy paving appearance and other findings along with their distribution in lung segments. Furthermore, to determine the CT-SS we divided each lung into 20 sub segments. The Linkert Score system of degree of 0,1 and 2 was provided. This indicates the intensity of involvement. It states that zero score indicates no involvement, whereas the Linkert figure 1 shows the involvement which is less than <50%. However, the remaining figure Linkert indicator figure 2 indicates the intensity of involvement if more than >50% by one zone. The total range of score for this test lies between 0-40. This score helps us to categories the patients based on their mild and severe cases. Here the score of less than <20 indicated mild infection, whereas, the score which appears more than >20 indicates the severity of the case. Results: The ground glass opacities which are trailed by consolidation of 49.4% and that of crazy paving by 21.64% was recorded as the most recognized finding. In most of the patients, the distribution of disease, with basal predilection, was recorded as bilateral, peripheral as well as multilobar. The ratio of vascular dilatation was recorded 19.5% and that of bronchiectasis was noted at 13.4% in patients. 3% of the patients showed the Halo, whereas reverse halo sign was noted in 1% of patients. None of the patients was seen to be carrying the Pleural effusion. Lung cavitation was seen in 2% of patients and isolated lobar consolidation without GGO was seen in 1% of patients. The segment which was most commonly involved bilaterally was the posterior segment of the lower lobes. As per the data collected from CT-SS, 80(82.4%) patients had mild and 17 (17.4%) patients had an acute disease symptoms respectively. Conclusion: GGOs are the most common imaging findings of COVID-19 pneumonia on HRCT chest having multilobar, bilateral and peripheral involvement with basal predilection. This proves CT-SS as a useful mechanism in placing pneumonia patients as mild and acute types. This helps categorizing the distinguishing the acute or severe patients from mild and to manage them accordingly.